DERIVATIONAL AND INFLECTIONAL AFFIXATION IN MENU-MENI DIALECT OF SASAK LANGUAGE - Sutarman Sutarman (Humanitatis : Journal of Language and Literature, 2017)
This research aims to investigate the derivational and inflectional affixation in Menu- Meni dialect of Sasak language. It includes in a qualitative research. The data are collected through interview, note-taking and self-introspection. The researcher also provides informants from the native speakers of Menu-Meni dialect in Tebao. The data collected are then analyzed using some steps- classifiying the data, identifying the forms of affixations, identifying the types of affixation, selecting the derivational and inflectional affixes and explaining the affixation on Menu-Meni dialect. The results show that there are three types of derivational and inflectional affixation in Tebao, namely prefix, suffix and confix. Derivational prefixes are /m-/, /ng/, /pǝ/, /bǝ/, and /n/. Derivational suffix include /-in/ and /-ang/. Derivational confix are /pe-q/, /be-an/, /pe-an/ and /kem-an/. Inflectional prefix includes /n/,/ng/,/m/, /te/, /be/ and /se/. inflectional suffix involves /-an/ and /-ang/ and inflectional confixes are /te-ang/,/te-in/, /be-an/, /pe-an/, /be-q/ and /kem-an/. Each form of derivation and inflection in Menu-Meni dialect has its own function.